INFORMATION MODEL OF MANUFACTURING AND TECHNOLOGICAL SOLUTION FOR PROCESS CONTROL SYSTEM OF MULTIPART PRODUCTION - Konstantin Vladimirovich Bashlayev (Advanced Engineering Research)
The efficiency improvement necessity of the technological process design for the multiproduct manufacture is proved. The information model of the liberal manufacturing and technological solution based on the standard technological systems application at the pre-production stages is offered and considered. The design method and the technology model structure providing a flexible synthesis of its elements at various stages of the production process are resulted. The virtual manufacturing operations application is proposed as system elements. Their compliance with intra- and interdepartmental operational order is considered. Particular focus is on the production planning phase, and on the necessity of the standard technological systems application for its speedup. Further technology system refinement is referred to the stages of planning and production where the workplaces are finally allocated for the operations. It is stated that the integration with the technical systems using rendition code tables is necessary. A special type of the manufacturing operation is selected for spoilage probability cases and for the process operations recurrence.